2006
DOI: 10.1017/s0022215106002702
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the incidence of facial palsy following parotidectomy performed by ENT and non-ENT surgeons

Abstract: Our complication rates were comparable with published results. There was no significant difference in the observed rate of post-operative facial nerve palsy and other known complications following parotid surgery performed by ENT and non-ENT surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…It is reassuring for both patients and surgeons that surgeon grade did not affect outcomes, and hopefully reflects standards of training within our teaching hospital trust. Eng and colleagues' findings regarding surgeon specialty concur with our own 9 …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It is reassuring for both patients and surgeons that surgeon grade did not affect outcomes, and hopefully reflects standards of training within our teaching hospital trust. Eng and colleagues' findings regarding surgeon specialty concur with our own 9 …”
Section: Discussionsupporting
confidence: 80%
“…Eng and colleagues' findings regarding surgeon specialty concur with our own. 9 Where it is available, continuous intra-operative electromyographic nerve monitoring has become something of a medicolegal necessity. However, Grosheva et al demonstrated in a prospective trial that intra-operative nerve monitoring did not decrease the incidence of post-operative facial nerve palsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salivary fistula was reported in 137 studies 6–10,12,14–16,18–24,27,28,30–34,36,38–40,43–45,47,49,51,52,55,56,58,62–65,75,76,79,84–87,89,91,93,97–99,101,103–109,112,114–119,124–127,129,131–133,136,138,139,141,144,148–150,153,154,156,164,166,170–215 reporting on 18,815 patients (Table I and Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, surgical excision or parotidectomy are also standard procedures for benign parotid tumors, with the exception of Warthin’s tumor in the elderly. However, according to a previous study by Eng et al , the incidence of temporary facial palsy following parotidectomy is 56–57%, and the incidence of permanent facial palsy is 2–7% (13). In addition, the risk of complication of parotidectomy greatly depends on the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%